Measurement of Mobilization Capacity via Actions Sequence Learning within Institutional Facebook Fan Pages - Cunha, Kaique Matheus R.; Gomes, Alan K. (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2019: Proceedings of the 25th Brazilian Symposium on Multimedia and the Web, 2019)
Within Online Social Networks, functionalities which allow the interaction among users are setting up network sociability practices. Actions such as Post, Comment, Like, Share, have a special meaning when focused by Digital Sociology. Our study is supported by Pierre Bourdie’s theory, searching for directions to identify and capture data related to sociability practices within Facebook fanpages. We use such data for actions sequence learning, and also, for the measurement the number of occurrences of the learned sequences. Our preliminary findings corroborate Bourdie’s theory, pointing out that the mobilization capacity is independent of the number of followers and, in addition, it is important to take into account the number of social interactions.